Set Up Time Reduction Using Single Minute Exchange of Dies (SMED) and 5S: A Case Study - Johan Krisnanto Runtuk (President University, 2021)
Manufacturing excellence represents the goal for every manufacturing industry all around the world. Reducing waste could help achieve manufacturing excellence since waste could happen in every manufacturing industry. PT. As one of the food and beverages industry, PT. MNO also focuses on reducing waste in the production process, especially in the filling department. Similar to other departments, the filling department also has planned and unplanned stoppages. As one of the planned stoppages, the setup activities represent one of the highest waste contributions in the filling department. Therefore, PT. MNO can reduce the setup time using the Single Minute Exchange of Dies (SMED) and 5S method. Then, the overall equipment effectiveness (OEE) calculation can show the differences between filling machine productivity before and after Single Minute Exchange of Dies (SMED) and the 5S method. As a result, the setup time is reduced from 34 minutes to 13 minutes by using the Single Minutes Exchange of Dies (SMED) method implementation. After the 5S method implementation, the setup time becomes ten minutes. The overall equipment effectiveness (OEE) calculation result shows better productivity after SMED and 5S method implementation in the filling department by the increasing OEE rate from 76% to 78% in the end. Keywords: Setup, waste, planned stoppages, Single Minute Exchange of Dies (SMED), 5S, Overall Equipment Effectiveness (OEE)